Differences in lesion interpretation between radiologists in two countries: Lessons from a digital breast tomosynthesis training test set. Issue 4 (23rd November 2021) - Li, Tong; Gandomkar, Ziba; Trieu, Phuong Dung (Yun); Lewis, Sarah J.; Brennan, Patrick C.
Abstract: Introduction: In many western countries, there is good evidence documenting the performance of radiologists reading digital breast tomosynthesis (DBT) images. However, the diagnostic efficiency of Chinese radiologists using DBT, particularly type of errors being made and type of cancers being missed, is understudied. This study aims to investigate the pattern of diagnostic errors across different lesion types produced by Chinese radiologists diagnosing from DBT images. Australian radiologists will be used as a benchmark. Methods: Twelve Chinese radiologists read a DBT test set and located each perceived cancer lesion. True positives, false positives (FP), true negatives and false negatives (FN) were generated. The same test set was also read by 14 Australian radiologists. Z‐scores and Pearson correlations were used to compare interpretation of lesions and identification of normal appearances between two groups of radiologists. Results: Architectural distortions ( p < .001) and stellate masses ( p = .02) were more difficult for Chinese radiologists to correctly diagnose compared to their Australian counterparts. Chinese readers categorised more FPs as discrete masses ( p < .001) and fewer FPs as architectural distortions ( p < .001) comparing with Australian radiologists. The percentages of FN for each cancer case were not correlated ( r = 0.37, p = .18) but the percentages of FP for each normal case were moderately correlated ( r = 0.52, p = .02) between two groups of readers. Conclusions: Architectural distortions and stellate masses were challenging to Chinese radiologists when reading DBT. Our findings proposed the need of development of training and education programs focussing on imaging cases tailored for specific groups of readers with certain interpretation patterns.